PENGARUH MINUMAN JAHE MERAH TERHADAP PERUBAHAN NYERI HAID PADA WANITA - Abidda, Lutfa Khoilil; Riamah, Riamah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Menstrual pain is something that is naturally experienced by women during menstruation, but menstrual pain has a normal limit, if the menstrual pain is excessive, it must be overcome (Bingan, 2021). One of the non-pharmacological therapies to treat dysmenorrhea is a red ginger drink. The purpose of this literature review is to determine the effect of red ginger drinks on changes in dysmenorrhea pain. The method used was a literature review, with a search on the PUBMED database and Google Scholar published from 2016 to 2021. keywords used were dysmenorrhea, red ginger, pain, menstruation, dysmenorrhea, and women. Twenty related kinds of literature were obtained. The results of the analysis of 20 journals illustrate that there is an effect of red ginger drink on changes in dysmenorrhea pain, for women from adolescence to early adulthood and even the elderly. By giving this red ginger drink, is expected to reduce menstrual pain in women.Keywords: Red Ginger, Dysmenorrhea, Pain, Women